Spatial distribution and source apportionment of soil heavy metals in the areas affected by non-ferrous metal slag field in southwest China - Jia, Liang; Liang, Huili; Fan, Min; Guo, Shushu; Yue, Tingting; Wang, Maosheng; Su, Mingyue; Chen, Shu; Wang, Zhe; Fu, Kaibin (Frontiers in Environmental Science, 2024)
The spatial distribution and source analysis of heavy metals in soil are of great significance for the risk assessment and control of heavy metal pollution.Herein, a total of 87 topsoil samples (0-30 cm) were collected in the areas adjacent to a non-ferrous metal slag field of Gejiu City, Yunnan Province. The typical heavy metal concentrations, available phosphorus, available potassium, ammonium nitrogen, nitrate nitrogen, and pH in each soil sample were determined. Based on the above basic data, distribution and origins of heavy metals was analyzed. The results indicated that the mean contents of Pb, As, Cu, Zn, Ni and Cr in the topsoil of the